Інноваційний аспект розвитку інтеграції України: Європейський союз та Митний союз - Пельо, А.Б. (Культура народов Причерноморья, 2013)
Стаття присвячена дослідженню конкурентних переваг і можливості інноваційного прориву в електронному розвитку фінансового ринку, які Україна може отримати інтегруючись у Європейський союз (ЄС) та Митний Союз (МС). Проаналізовано сучасний стан інформаційно-телекомунікаційного забезпечення фінансового сектору ЄС, країн МС та України. Розглянуто фактори інноваційної трансформації фінансового простору України. Статья посвящена исследованию конкурентних преимуществ и возможностей инновационного прорыва в электронном развитии финансового рынка, которые Украина может получить интегрируясь в ЕС или ТС. Проанализировано современное состояние информационнотелекоммуникационного развития финансового пространства ЕС и ТС а также возможности интеграции Украины в него. The paper investigates competitive advantages in electronic development of financial sector that Ukraine may get after closing to the European Union (EU) or the Customs Union (CU). The telecommunication’s support of the financial sector of European Union, Customs Union and Ukraine are analyzed and compared. Also the innovative transformation factors of the financial environment of Ukraine provided by EU and CU are determined. Basically, it is concluded that Ukraine takes more competitive advantages from Western vector rather than Eastern in the term of innovative aspects of economic functioning. One of the most important reasons of it is that EU has already strong developed electronic infrastructure of economy that still has to be done by Customs Union.